Emotional intelligence and interpersonal relationship among young adults in Kota Samarahan - Nur Jasmine, Rakawi (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study identified the relationship between emotional intelligence and interpersonal relationships. Survey data from young adults were analyzed using developed multidimensional instrument emotional intelligence and interpersonal relationships. The questionnaires used for emotional intelligence was Schutte‟s Self-Report Inventory (SSRI) (1998) and Callaghan‟s Flat-Q Interpersonal Relationships (2014) for interpersonal relationships. Independent t-test was used to examine the significant difference between male and female in emotional intelligence and interpersonal relationships. Pearson Correlation was used to identify relationship between emotional intelligence and interpersonal relationships. The findings showed a relationship between emotional intelligence and interpersonal relationships among young adults in Kota Samarahan, Sarawak. The findings also showed a difference in emotional intelligence by age. However, no difference in emotional intelligence found by gender and ethnic. On the other hand, there was a difference in interpersonal relationships by gender and ethnic. However, no difference in interpersonal relationship by age.